TINJAUAN YURIDIS TERHADAP PEMUTUSAN HUBUNGAN KERJA AKIBAT COVID-19 SEBAGAI ALASAN MEMAKSA FORCE MAJEURE (STUDI PUTUSAN NO 134/PDT.SUS-PHI/2021/PN JKT.PST) - Anjelina, Paramita; Wijayati, Ani; A.M. Pandiangan, L. Elly (Fakultas Hukum Universitas Kristen Indonesia, 2024)
The global impact of the Covid-19 pandemic has been substantial, particularly affecting the health and economic sectors across all countries. The virus's swift spread has resulted in heightened domestic activities, influencing the economy and disrupting businesses, employment, and overall social life. The Indonesian government has officially acknowledged the pandemic as a national crisis and emergency. In summary, the Covid-19 pandemic has deeply affected various facets, encompassing health, the economy, social interactions, and employment. To address this crisis, the government has implemented measures to mitigate its effects and safeguard the safety and welfare of the workforce. This study uses a method of normative jurisprudence with a legal approach (Statute Approach) and a case approach. (Case Approach). The library materials used in this writing are laws, court rulings, books, journals, websites and so on related to Covid-19, termination of employment, and force majeure. The findings of this research indicate that a company undergoing the challenges of the Covid-19 pandemic doesn't automatically qualify for force majeure; the company is required to demonstrate that the pandemic significantly impacts the viability of its operations, necessitating certain actions. Additionally, the rights of the workers must be upheld in such cases, ensuring their well-being and satisfaction. In legal proceedings, judges are tasked with enforcing the law in accordance with the principles of justice and the rule of law.